“The first will serve the bookseller’s purpose”: Sterne’s double title page in The Sermons of Mr. Yorick - Hartvig, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2018)
The notices of new publications in magazines and newspapers were part of the marketing policy of publishers. The wording and format of these advertising columns in the, mainly London, newspapers reveal much about the sophisticated manner in which the editors communicated their purpose in marketing newly published books. Besides the reviews, it is here, in these brief notices and advertisements, that we can map out barely noticeable shifts in the early reception of Sterne’s fiction and his sermons (see Brandtzæg et al., “Advertising” 28). Digital archives such as ECCO, the Burney Collection, and British Periodicals are of great help today.